Perancangan Prototipe Sistem Monitoring dan Kontrol Hidroponik Pada Tanaman Selada Berbasis Internet of Things - sadrina; T. Adrian Refriansyah; Malahayati; Roji April Naldi (Politeknik Aceh, 2023)
Indonesia is located in a tropical area and is rich in natural resources and abundant agricultural land. The technique that can save land is the hydroponic system. The hydroponic system has the disadvantage that it requires more labor and maintenance compared to tillage. This research aims to design a tool that can combine and control air pH, air nutrients, air temperature and air flow speed on hydroponic plants through the Blynk application. It is hoped that this application can make it easier for hydroponic owners to control and monitor their plants remotely. The method used in this research is a descriptive method with a Waterfall research design. Based on the research results, the results of testing the air pH sensor showed an average difference of 0.18 and testing the TDS sensor, temperature sensor and water flow sensor produced different types of air which had their own resulting values in the sensor readings. In testing the relay response, applying voltage to the relay and calculating the length of delay on the pump relay gives different times with a calculation of several seconds